USO DE LA REV-1 EN EL CONTROL DE LA BRUCELOSIS OVINA EN UNA EMPRESA OVEJERA DEL PERÚ - Rondón E., Juan (2002)
In 1996, after a 5 year hiatus, the use of the Rev-1 vaccine was reintroduced to control ovine brucellosis (Brucella ovis) in a large sheep company of the central Peruvian Andes, and by the year 2000, 86.3% of the rams (3,284 of 3,804) and 100% of the young males (n=1,811) were vaccinated. During the shearing campaign for year 2000, testicles of the entire male breeding population (n=5,615) were examined manually and 320 blood samples (214 rams and 106 yearlings) were taken for AGID testing to determine the presence of Brucella ovis antibodies. Epididymitis lesions were found in 89.4 x 10,000 of the rams and 38.6 x 10,000 of the yearlings, compared to 817 x 10,000 for rams and 214 x 10,000 for yearlings prior to reintroduction of Rev-1 vaccination. The progressive reduction in epididymitis was directly related to vaccination. The level of infection was found 1,186.4 x 10,000 in 1996 decreasing to 531.2 x 10,000 in 2000, but infection levels remained high in the vaccinated population (635.8 x 10,000). Clinical expression of the disease was 38.5 x 10,000 in unvaccinated males compared to 97.4 x 10,000 in vaccinated animals, but infection rates were considerably lower in vaccinated (635.8 x 10,000) than in unvaccinated (1,219 x 10,000) males. These results clearly demonstrate the efficaciousness of Rev-1 in controlling epididymitis in rams. Combined use of the Rev-1 vaccine with periodic clinical examinations, annual serological tests and the elimination of all reactors is recommended, but vaccination alone at a national level would help in controlling this highly prevalent disease in the Peruvian sheep population.